Dampak Kesehatan Fisik, Mental dan Sosial pada Penggunaan Minuman Keras Di Kalangan Remaja (Studi kasus di Kabupaten Mamasa) - Suryadi, Suryadi; Novtalya, Novtalya (Yayasan Mandar Indonesia, 2024)
Alcohol use among adolescents is a worrying phenomenon with significant impacts on physical, mental, and social health. This study aims to analyze the impact of alcohol use on adolescent health through a case study approach. The research method used is qualitative descriptive with in-depth interviews with five adolescent alcohol users in Mamasa, West Sulawesi, as well as direct observation. Data were analyzed using a thematic approach to identify key patterns related to health impacts. The results showed that alcohol use in adolescents causes health problems such as impaired liver function, decreased immunity, and cognitive problems. In addition, changes in social behavior were found, including aggressiveness, impaired family relationships, and involvement in risky behavior. Causal factors include peer pressure, social environmental influences, and lack of family supervision. The conclusion of this study emphasizes the need for holistic interventions, involving health education, active family roles, and strict policies in controlling access to alcohol in adolescents. These findings are expected to be the basis for developing effective prevention programs to minimize the negative impacts of alcohol use among adolescents.